The association of post-traumatic stress disorder and cognitive factors : long-term memory, short-term memory and working memory - Hulda María Frostadóttir 1989- (2021)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder that individuals may develop after a traumatic event. The aim of this study was to examine cognitive function of individuals with PTSD symptoms. The hypothesis was that the performance of individuals who met criteria for PTSD would be poorer on task measuring working memory and memory compared to a control group. Participants were 48 volunteers, both psychology students and employees at Reykjavík University. They were divided into two groups according to their scores on the PCL-5 list, which measures PTSD symptoms, and thirteen participants met the criteria for PTSD. Three cognitive tests were used to compare the memory and working memory of these two groups, Operation Span task, Digit Span and Logical Memory test. The results showed that the PTSD group scored significantly lower on a test of long-term memory. There was not a significant difference in performance on other measures but a trend towards worse performance among the PTSD group on all tests except for Digit Span forward which, examined short-term memory. These results suggest that long-term memory is poorer in individuals with PTSD, but further research in larger groups are needed to understand the association of PTSD and cognition better. Keywords: PTSD, Memory, Long-term memory, Short-term memory, Working memory, Digit span, Operation span, Logical Memory, PCL-5 Áfallastreituröskun er geðröskun sem einstaklingur getur upplifað eftir ýmiskonar áföll. Markmið þessarar rannsóknar var að skoða hugræna virkni hjá einstaklingum með PTSD. Tilgátan var að frammistaða þeirra sem uppfylltu skilyrði um PTSD yrði lakari á verkefnum sem mældu vinnsluminni og minni samanborið við samanburðarhóp. Þátttakendur voru 48 sjálfboðaliðar, bæði nemendur og starfsmenn við Háskólann í Reykjavík. Þátttakendum var skipt í tvo hópa eftir skori þeirra á spurningalista sem mat einkenni áfallastreituröskunar (PCL-5 list), og uppfylltu þrettán þáttakendur skilyrði um áfallastreituröskun. Notast var við þrjú hugræn ...